Effects of hemodynamic monitoring using a single-use transesophageal echocardiography probe in critically ill patients – study protocol for a randomized controlled trial - Cioccari, Luca (Trials, 2018)
BACKGROUND: Hemodynamic instability is one of the leading causes of intensive care unit (ICU) admission. Early stabilization of hemodynamics is associated with improved outcome. The monitoring used to guide hemodynamic support may influence the time needed to achieve stable hemodynamics. Visualization of the heart using echocardiography offers the advantage of direct measurement of cardiac volumes and ventricular function. A miniaturized monoplane transesophageal echocardiography (TEE) probe was developed, allowing for almost continuous qualitative hemodynamic TEE assessment (hTEE) after brief bedside training. The primary objective of the study is to assess whether hemodynamic monitoring using the hTEE technology shortens time to resolution of shock in ICU patients in comparison to standard monitoring using a central venous catheter, pulmonary artery catheter, or conventional echocardiography. METHODS: Five hundred consecutive subjects with circulatory shock (low mean arterial blood pressure (MAP) and signs of organ hypoperfusion) at the time of ICU admission are included in the study. The subjects are randomly assigned to one of four groups using a 2 × 2 factorial design stratified by method of hemodynamic monitoring (hTEE vs standard hemodynamic monitoring) and frequency of hemodynamic assessments (minimum every 4 h vs standard of care). The primary study outcome is the time from study inclusion to resolution of circulatory shock, defined as MAP >  60 mmHg for ≥ 4 h after discontinuation of vasopressors and inotropes. The hTEE monitoring consists of the acquisition of three defined echocardiography views: Transgastric mid-esophageal short axis with measurement of fractional area change of left ventricle, mid-esophageal four-chamber view with measurement of the ratio of right to left ventricular area, and mid-esophageal ascending aortic short-axis view with measurement of the superior vena cava collapsibility index. In the control groups, monitoring modalities, including conventional TTE and TEE but not hTEE, are at the discretion of the treating physician. The interpretation of hemodynamic monitoring and the subsequent changes in patient management are recorded after each hemodynamic assessment. Differences in the primary and further secondary time-to-event outcomes will be assessed using a competing risk model accounting for the competing risk of death. DISCUSSION: The effect of using echocardiography as a monitoring modality on relevant patient outcomes has not been established so far. The study at hand may be one of the first trials to provide detailed data on effectiveness and safety of echocardiography to guide treatment in patients with circulatory shock. TRIAL REGISTRATION: ClinicalTrials.gov, ID: NCT02048566. Registered on January 29, 2014.  ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-2714-4) contains supplementary material, which is available to authorized users.